PENERAPAN TEKNIK THINK-PAIR-SHARE UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK SISWA PADA MATERI CERITA PERISTIWA - Haqimurosyad, Asep Ikhsan; Iswara, Prana Dwija; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2017)
In the first observation to 5th grade at SDN Kertawinangun I, there are some problem about planning, implementation, student activities, and result learning on the story of case. Either way, there are need solving all that problems. The reason of implementation this research is to improve the listening ability.Â  The goals of this research are to know the learning plan using think-pair-share technique, the implementation of think-pair-share technique, student activities, and learning result from the application think-pair-share technique. This research using Classroom Activity Research (PTK). The instrument that used in this research are guidelines of teacher performance observation, guidelines of student activity observation, guidelines of interview, field notes, and question. The result improvement of this research, seem from the first cycle until the last cycle. In the planning aspect, the 1st cycle result reach 68%, the 2nd cycle reach 79%, and the 3rd cycle reach 87%. Then, in the implementation aspect, the 1st cycle reach 66%, the 2nd cycle reach 80%, and the 3rd cycle reach 88%. Except that, there is the student activity improvement. In the 1st cycle, the result reach 11,76%, the 2nd cycle reach 50%, and the 3rd cycle reach 85%. The learning result also shows the improvement. In the 1st cycle, the result reach 38%, the 2nd cycle reach 62%, and the 3rd cycle reach 85%. So, the application of think-pair-share technique can be improve the listening ability on the story of case.